Rancang Bangun Sistem Penerimaan Siswa Baru Berbasis Website pada UPT SMPN 4 Satap Malangke - Sukmawati Sukmawati; Nur Annisa; Alfhian Makmur; Sigit Irawan Tamrin (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This study aims to design and build a website-based new student admission system. The method used is Research and Development (R&D) with a waterfall development model, through the stages of analysis, design, implementation, testing, and maintenance. Data collection was carried out through direct observation, interviews with the school, and literature studies. The system was developed using PHP Native, MySQL, and Bootstrap with the help of the Visual Studio Code editor. The new student admission process at UPT SMPN 4 Satap Malangke is still done manually, causing obstacles such as file accumulation, recording errors, and lack of time and energy efficiency. The solution offered is an online system that allows prospective students to register, fill out forms, and upload documents without having to come to school. Admin can verify data more quickly and accurately. The test results using the black box method showed that all system functions were running well. Validation by system experts obtained an average score of 3.69 and by practitioner experts of 4.00, both in the "Very Eligible" category. Meanwhile, testing from 29 respondents obtained a percentage of 78.4% in the "Good" category.